Islamic Foundations of Multicultural Education: Insights from the Qur’an, Hadith, and Ibn Kathīr’s Tafsir - Onwardono Rit Riyanto; Siti Fatimah; Siti Nur Millah; Renaldy Bagas Saputra; Afryandi Pamungkas (Journal of General Education and Humanities, 2025)
Despite extensive discussions on multiculturalism in education, few studies explore its foundations from an Islamic perspective, particularly through classical tafsir and authentic hadith. This study addresses this gap by uncovering the principles and values of multicultural education in Islamic teachings through an analysis of the Qur'an based on Ibn Kathīr's Tafsir and the hadiths of the Prophet Muhammad SAW. The research employs a qualitative literature review approach, drawing primary data from Ibn Kathīr’s Tafsir and collections of authentic hadiths, and secondary data from Islamic and multicultural education literature. The findings reveal that the Qur'an and hadith contain strong principles of multiculturalism, including recognition of diversity, social justice, respect for human rights, and the promotion of cross-cultural dialogue. Ibn Kathīr’s Tafsir emphasizes that diversity is sunnatullah to be approached with wisdom and insight. Sources from the Qur'an that highlight these principles include Q.S. Al-Hujuraat: 13, Ar-Rūm: 22, Al-Maidah: 8, Al-Mujadalah: 11, An-Nisa: 135, Al-Baqarah: 178, Al-A'rāf: 199, and Al-Muthaffifin: 29. Relevant hadith include Sahih Bukhari no. 1376, Sahih Muslim no. 2564, Sunan Tirmidhi no. 3890, Ahmad no. 8595, Musnad Ahmad no. 15444, Sunan Ibn Majah no. 68, and Sunan Tirmidhi no. 520. These findings provide a conceptual framework for educators to design learning environments and curricula that actively respect and accommodate ethnic, cultural, and religious differences, fostering peaceful coexistence and moral integrity in schools. This research is a scholarly reference for integrating Islamic values into multicultural education practices.